Boundary Value Problem for Nonlinear Implicit Generalized Hilfer-Type Fractional Differential Equations with Impulses. (21st April 2021) - Salim, Abdelkrim; Benchohra, Mouffak; Lazreg, Jamal Eddine; N'Guérékata, Gaston
Abstract : This article deals with some existence, uniqueness, and Ulam-Hyers-Rassias stability results for a class of boundary value problem for nonlinear implicit fractional differential equations with impulses and generalized Hilfer Fractional derivative. The results are obtained using the Banach contraction principle and Krasnoselskii's and Schaefer's fixed-point theorems.